IMPLEMENTASI ALGORITMA SPRITZ DAN SPREAD SPECTRUM UNTUK MENYEMBUYIKAN PESAN ENKRIPSI KEDALAM FILE AUDIO MP3 - Muhammad Iqbal; Taronisokhi Zebua; Ronda Deli Sianturi (STMIK Budi Darma, 2019)
Optimizing the security of confidential text messages is very important to protect the contents of messages from those who want to use or damage the message. The use of cryptographic techniques in securing data can still raise suspicion of the message that has been secured. This study explores how to use steganography techniques to coat encrypted message security based on steganography techniques. The spritz algorithm is a cryptographic algorithm that is used to obtain the cipher from the original message, while the spread spectrum method is a method used to hide the original data password into an image. Based on testing done by combining these two techniques, it is quite reliable to optimize the security of secret messages because others cannot see the existence of the cipher of the original data in plain sight.Keywords: Cryptography, Steganography, Spritz, Spread Spectrum, mp3